MECHANISMS FOR DEVELOPING INDIVIDUAL EDUCATION PLANS WITH STUDENTS WITH SPECIAL NEEDS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article analyzes the organizational and pedagogical mechanisms for developing an individual education plan (IEP) for students with special needs. The importance of an individual approach in inclusive education, diagnostic stages, goal setting, development of adapted curricula, and monitoring mechanisms are highlighted. According to the results of the study, the systematic development of an individual education plan helps to increase students' learning outcomes and the level of social adaptation.